2002
DOI: 10.1177/009145090202900204
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication and Rite of Passage to Adulthood in Norway

Abstract: The author describes young Norwegians' use of alcohol in “russefeiring,” a special rite of passage to adulthood in the form of prolonged graduation parties. In this ritual, the young people wear special clothes, celebrate, and drink beer and spirits from the 1st through the 17th of May. The article argues that young people have invented rites of passage in which expressive individualism is stressed as a value. The article discusses the use of symbolic anthropology and sociology and field methods in research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 8 publications
0
31
0
1
Order By: Relevance
“…School Leavers Festivals are often referred to as 'a rite of passage' from youth to the community of adulthood at the end of secondary education (Winchester, McGuirk, & Everett, 1999;Sande, 2002). Reports from SFs in South Australia and Queensland state that most Schoolies expect to be drunk most/every night of the holidays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…School Leavers Festivals are often referred to as 'a rite of passage' from youth to the community of adulthood at the end of secondary education (Winchester, McGuirk, & Everett, 1999;Sande, 2002). Reports from SFs in South Australia and Queensland state that most Schoolies expect to be drunk most/every night of the holidays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Exploring the various meanings of intoxication, Sulkunen (2002: 272) concluded that images of intoxication are 'a powerful device in people' s articulations of their social relationships, aspirations and values. ' Sande (2002) investigated Norwegian youths' use of alcohol in 'russefeiring', a special rite of passage to adulthood that consists of extended graduation parties involving alcohol consumption. Alcohol was found to be a key symbol in the ritual process, offering an opportunity to communicate meaning between subculture members and the wider society.…”
Section: Alcohol and Subculturesmentioning
confidence: 99%
“…Alcohol is often researched in leisure as related to health (Denzin, 1987;Wechsler, Dowdall, Davenport, & Castillo, 1995;Smeaton, Josiam, & Dietrich, 1998), as a deviant form of leisure (Sande, 2002;Shinew & Parry, 2005;Stebbins, 2007), or as an enhancement to the leisure experience Downloaded by [University of York] at 22:10 04 June 2016 (Carruthers, 1993;Simpura, 1985). However, with the exception of a few studies (Faulkner, 1991;Purcell & Graham, 2005;Stratton, 1985;Young, 1971Young, , 1974, leisure experiences that include alcohol as an important component in the construction of leisure subcultures, and their accompanying leisure environments, have largely been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…There is certainly evidence that young people have forged their own rites of passage (Sande, 2002), and that activities such as nightclubbing and alcohol consumption are central to such transitions. Delaney (1995), for example, suggests that Anglo-American adolescents try to enact their own rite of passage through indulging in adult behaviour such as drug-taking, alcohol consumption and sexual intercourse.…”
Section: The Transitional Context Of Young Adults" Clubbing Practicesmentioning
confidence: 99%